Impact of Quality Management Techniques and System Effectiveness on the Green Supply Chain Management Practices - Kittisak Jermsittiparsert; Puttisat Namdej; Thanaporn Sriyakul (International Journal of Supply Chain Management, 2019)
Nowadays organizations are facing multiple challenges such as survival in competitive dynamic and competitive environment, meet the customer needs and the impact of their action on the environment are the few ones to name. Sustainability has triggered the need for the companies to revisit their supply chains to cope up with the environmental needs and one of the major demand from the customers as well. In this regard the present study has examined the impact of quality management techniques and system on the green supply chain management practices. The study has explored the JIT, TQM and quality management system effectiveness as a potential driver for the green supply chain management practices. The data were collected from the procurement managers which were working in the auto parts manufacturing industry. Smart PLS was used for the data analysis. Results of the study revealed a significant link between all the independents (TQM, JIT and quality management system) and dependent variable (green supply chain management practices). The direction of all the relationships was positive. However, according to the results TQM was the strongest predictor for the green supply chain management practices.